Identification and Evaluation of Recombinant Outer Membrane Proteins as Vaccine Candidates Against Klebsiella pneumoniae - Zhang, Bao-Zhong; Hu, Danyu; Dou, Ying; Xiong, Lifeng; Wang, Xiaolei; Hu, Jingchu; Xing, Shao-Zhen; Li, Wenjun; Cai, Jian-Piao; Jin, Meiling; Zhang, Mengya; Lin, Qiubin; et al. (Frontiers in Immunology, 2021)
Klebsiella pneumoniae found in the normal flora of the human oral and intestinal tract mainly causes hospital-acquired infections but can also cause community-acquired infections. To date, most clinical trials of vaccines against K. pneumoniae have ended in failure. Furthermore, no single conserved protein has been identified as an antigen candidate to accelerate vaccine development. In this study, we identified five outer membrane proteins of K. pneumoniae, namely, Kpn_Omp001, Kpn_Omp002, Kpn_Omp003, Kpn_Omp004, and Kpn_Omp005, by using reliable second-generation proteomics and bioinformatics. Mice vaccinated with these five KOMPs elicited significantly higher antigen-specific IgG, IgG1, and IgG2a. However, only Kpn_Omp001, Kpn_Omp002, and Kpn_Omp005 were able to induce a protective immune response with two K. pneumoniae infection models. These protective effects were accompanied by the involvement of different immune responses induced by KOMPs, which included KOMPs-specific IFN-γ-, IL4-, and IL17A-mediated immune responses. These findings indicate that Kpn_Omp001, Kpn_Omp002, and Kpn_Omp005 are three potential Th1, Th2, and Th17 candidate antigens, which could be developed into multivalent and serotype-independent vaccines against K. pneumoniae infection.